Quantitative Evaluation Research and Its Implications for the Development of Islamic Education. - Fahriah Fahriah; Nuril Huda; Dina Hermina; Hamrani Hamrani (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to describe quantitative evaluation research and its implications for the development of Islamic education in Indonesia. The research was conducted through library research by reviewing literature that discusses educational evaluation models and theories such as CIPP, Goal-Oriented, Goal-Free, and Kirkpatrick, as well as relevant policy documents from educational institutions and the Ministry of Religious Affairs. The analytical approach used is descriptive-analytical, including the identification of key concepts, classification of evaluation approaches, and synthesis of implications for educational practice and policy. The findings indicate that quantitative evaluation research plays a strategic role in systematically and measurably assessing the effectiveness of educational programs and policy interventions. It provides empirical evidence to strengthen institutional accountability, support evidence-based decision-making, and encourage continuous improvement in educational management. In practice, the application of appropriate evaluation models enables Islamic educational institutions to measure the impact of programs such as Madrasah Digital Transformation, Religious Moderation, and Religious Literacy Assessment, thereby strengthening monitoring and follow-up mechanisms.